2013
DOI: 10.3389/fimmu.2013.00154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights for Optimizing T Cell Receptor Specificity Against Cancer

Abstract: Cytotoxic CD8 T cells mediate immunity to pathogens and they are able to eliminate malignant cells. Immunity to viruses and bacteria primarily involves CD8 T cells bearing high affinity T cell receptors (TCRs), which are specific to pathogen-derived (non-self) antigens. Given the thorough elimination of high affinity self/tumor-antigen reactive T cells by central and peripheral tolerance mechanisms, anti-cancer immunity mostly depends on TCRs with intermediate-to-low affinity for self-antigens. Because of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 128 publications
0
37
0
Order By: Relevance
“…Experimentally generated high-affinity TCRs might be advantageous by boosting effector function and proliferation, thereby persisting longer and in larger numbers as compared with T cells with low-affinity TCRs, but they may also bear an increased risk of unwanted toxicities (3,4,(9)(10)(11)(12). Low-avidity T cells would gain value if their effector functions could be enhanced, as they are reported to be less susceptible to tolerization and may represent a lower toxicity risk (3,4,13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally generated high-affinity TCRs might be advantageous by boosting effector function and proliferation, thereby persisting longer and in larger numbers as compared with T cells with low-affinity TCRs, but they may also bear an increased risk of unwanted toxicities (3,4,(9)(10)(11)(12). Low-avidity T cells would gain value if their effector functions could be enhanced, as they are reported to be less susceptible to tolerization and may represent a lower toxicity risk (3,4,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is consensus that durable antitumor responses require highly active T cells, it is not clear how this is best achieved. At least two major impediments have been identified that impinge upon achieving this prerequisite: inherent intermediate-to low-affinity T-cell receptors (TCR) of antitumor T cells that may not mount a successful tumor-specific response (3,4), and functional inactivation of T cells in the tumor milieu (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The functional avidity of T cells is primarily controlled by the strength of TCR-pMHC interactions, a key parameter shown to impact on numerous aspects of T cell biology, including their thymic selection (21), activation and differentiation (22), autoimmune pathogenicity (23), and protection against infection and cancer (24). In fact, TCR-pMHC binding avidity may offer a key metric by which the quality of the T cell response can be directly evaluated, since it controls T cell activation, differentiation, and functional efficacy (25).…”
Section: Introductionmentioning
confidence: 99%
“…5B) were stable over time (data not shown). Theoretically, higher intensity tetramer staining could be associated to a higher expression at the surface level of the TCR and/or the co-receptor (CD4), and/or to a higher TCR avidity (35,36). We next measured the expression level of TCR and CD4 separately, in order to avoid competition of the staining antibodies.…”
Section: Characterization Of Two Distinct Mage-a3-specific Cd4 T-cellmentioning
confidence: 99%